Quantifying, Understanding and Enhancing Relational Continuity of Care (QUERCC): a mixed-methods protocol - Panagiotis Kasteridis; Tom Marshall; Krishnarajah Nirantharakumar; Sheila Greenfield; Brian H Willis; Fiona Scheibl; Iestyn Williams; Kamil Sterniczuk; Jinyang Chen; Zecharias Fetene Anteneh (BMJ Open)
Introduction Relational continuity of care is where patients see the same clinicians over time. Evidence suggests relational continuity of care is valued by patients and clinicians and results in better health. While current National Health Service policy aims to maintain relational continuity of care, it has been declining in recent years, which may be linked to the growth in practice size, increased staff turnover, part-time working and the focus on patient access. Our research aims to develop resources to help clinicians measure, manage and improve relational continuity of care.Methods and analysis A mixed-methods approach in UK primary care commencing with two workshops drawing patients, clinicians and researchers together to establish an agreed approach on the measurement of continuity of care. Second, analysis of national data will provide insight into how staff turnover, part time working, practice size and funding per patient affects continuity. Third, case studies in a sample of high-performing practices will document the barriers and facilitators to the establishment and maintenance of continuity of care. Fourth, an economic analysis of resource costs and health outcomes using linked primary and secondary care data will show whether costs influence continuity for different patient groups (by age, sex, deprivation status and chronic disease status). Fifth, we will develop practical guidance for clinicians to improve continuity of care, based on the findings from each stage of the research.Ethics and dissemination The study has approval from HRA Health and Care Research Wales Research Ethics Committee (HCRW). Findings will be disseminated through peer-reviewed publications, participatory workshops, podcasts, clinical networks and academic conferences.